Strategi pendidik dalam mengembangkan peran peer group untuk meningkatkan perkembangan sosial anak usia dini di lingkungan sekolah - Serdaningtyastuti Ririn Hariani (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
This paper aims to describe the strategic approach of educators in developing therole of peer groups to improve the social development of early childhood in the schoolenvironment. The results of the discussion by streamlining the role of each group member sothat group dynamics can really be realized as expected, with supervision from educators so thatthe expected goals are achieved. Friends can provide peace when experiencing worries. Forthis reason, from an early age children need to be invited to be realistic about themselves andtheir abilities. That's why in peer groups, children can learn the rules governing the roles ofpeople who are equal and also learn the values of justice. Thus, the need to relate to the socialenvironment as well as the need for achievement and self-reflection can both be satisfied.